Coupled discrete/continuum simulations of the impact of granular slugs with clamped beams: Stand-off effects. (January 2018) - Goel, A.; Uth, T.; Liu, T.; Wadley, H.N.G.; Deshpande, V.S.
Highlights: Simulations performed for impact of granular slug on deformable beams. Slug evolution strongly dependent on inter-particle stiffness. Pressure applied to the beams from the slug decreases with increasing stand-off. Stand-off dependence arises from the lengthening of slugs. Abstract: Coupled discrete particle/continuum simulations of the normal (zero obliquity) impact of granular slugs against the centre of deformable, end-clamped beams are reported. The simulations analyse the experiments of Uth et al. (2015) enabling a detailed interpretation of their observations of temporal evolution of granular slug and a strong stand-off distance dependence of the structural response. The high velocity granular slugs were generated by the pushing action of a piston and develop a spatial velocity gradient due to elastic energy stored during the loading phase by the piston. The velocity gradient within the "stretching" slug is a strong function of the inter-particle contact stiffness and the time the piston takes to ramp up to its final velocity. Other inter-particle contact properties such as damping and friction are shown to have negligible effect on the evolution of the granular slug. The velocity gradients result in a slug density that decreases with increasing stand-off distance, and therefore the pressure imposed by the slug on the beams is reduced with increasing stand-off. This results in the stand-off dependence of the beam's deflection observed by Uth et al. (2015) . The coupled simulations capture both the permanent deflections of the beams and their dynamic deformation modes with a high degree of fidelity. These simulations shed new light on the stand-off effect observed during the loading of structures by shallow-buried explosions.